A preliminary study on the acceptance of assistive devices among elderly in dementia day care centre in Malaysia - Ahmad Safawi, Nur Balqis; Abdul Rahim, Asiah; Hj. Zen, Ismawi (UniversityPublications.net, 2014)
Assistive device is a tool used to ease people in everyday life especially those with the cognitive illnesses. Nowadays, assistive devices have widely been used in many countries as a way to increase their quality of life. The aim of this paper is to seek the experience and reaction of the dementia elderly in Malaysia with their usage of assistive devices. For this research, qualitative and quantitative methods were implemented in collecting data. Questionnaire, observation, checklist and interview session were the tools used throughout the research.